Evaluation of the yield performance of lettuce cultivars in aquaponic and hydroponic systems - Sutani, Jussara; Sossae, Flávia Cristina; Castro, Marcus Cesar Avezum Alves; Sousa Junior, Gilmar da Silveira (Science & Technology Journals, 2021)
Healthy food and environmental awareness drive research focused on food production in integrated systems. The research evaluated the development of lettuce cultivars in hydroponic and aquaponic systems. The experiment was conducted in a 4x2 factorial scheme, evaluating four lettuce cultivars (crespa, americana, roxa and lisa) in five repetitions. It was conducted in a greenhouse applying the NFT technique, transplanting 40 total lettuce seedlings. In the hydroponic system, nutrient solution was used, and in the aquaponic system an efficient technique was applied with biomass proportion (kg) of tilapia fish. The abiotic parameters of water and environment were measured daily. In both systems the agronomic characteristics of the cultivars were analyzed: total number of leaves, total moist mass (g), fractional moist mass (leaves, stem and root) (g) and dry mass of the leaves. The hydroponic system showed better performance in all data collected. Lettuces developed in both systems; the lisa cultivar reached the highest number of leaves; and the americana cultivar obtained the highest total fresh mass. Regarding the dry mass, the cultivars crespa, americana and lisa did not differ statistically. In the aquaponic system, the nutrients were derived from the fish feed and waste, in a natural and continuous way, and that system may be more financially viable because it produces two products.
Keywords: Lactuca sativa L.; fresh mass; dry mass; nutrients; tilapia